Gambaran Sistem Pemusnahan Obat Kadaluwarsa di Logistik Farmasi RSUD Mohammad Natsir Solok Tahun 2025 - Anzalna Razak; Erpidawati Erpidawati; Yuliza Anggraini (Corona: Jurnal Ilmu Kesehatan Umum, Psikolog, Keperawatan dan Kebidanan, 2025)
Introduction the management of expired drugs is an important part of the hospital's pharmaceutical logistics system to ensure the safety of patients, staff, and to protect the environment. The purpose of this study is to evaluate the implementation of procedures for returning expired drugs to the manufacturer or pharmaceutical company, as well as to examine the expired drug disposal system, particularly the methods of direct disposal to the Final Disposal Site (TPA) and open burning at RSUD Mohammad Natsir Solok. However, the implementation in the field has not been entirely effective. The method used in this study is a qualitative descriptive approach, with data collection techniques including observation, interviews, and documentation. The approach involved several informants who were directly involved in pharmaceutical logistics management in order to obtain in-depth and relevant data. The results of the study show that the hospital has not carried out expired drug destruction using the methods of direct disposal to the TPA or open burning. No clear information or official documentation was found regarding the use of these two methods. Informants stated that even if such methods were used, they occurred in the past and were not formally documented. The conclusion of this study is that open burning and direct disposal to the TPA have not become part of the expired drug management system at RSUD Mohammad Natsir Solok. The recommendation of this research is the development of clear operational procedures and increased staff awareness regarding the importance of safe and standard-compliant pharmaceutical waste managemen